Pregnancy in a Renal Transplant Patient-when unsafe - Khanam, Khaleda; Ara, Anjuman; Begum, Mosha Hafsa; Rayen, Junnu; Khanum, Shakila; Rashid, Harunur (Northern International Medical College Journal, 2016)
Abstract not available Northern International Medical College Journal Vol.7(2) Jan 2016: 153-155